Physical exercise and emotional state in CrossFit® practitioners during the COVID-19 pandemic (Research, Society and Development, 2024)
The COVID-19 pandemic brought several changes of habits due to restrictions set by government orders. The physical activity was affected and impacted on different levels the life of people, amongst them, CrossFitters. This study has the objective of evaluating the physical activity levels and emotional state of CrossFitters during the COVID-19 pandemic. The research was made through questionnaire send via Google Forms link, in which the questionnaire contains sociodemographic data, physical activity, IPAQ-SF (International Physical Activity Questionnaire - Short Form) e DASS-21 (Depression Anxiety and Stress Scale - Short Form). The results of the research shown the consumption of alcohol and e-cigarettes were affected by the pandemic, reduction, even if small, in physical activities levels and emotional state negatively affected due to trauma caused by several restrictions and emotions develop during this period.